المعاجم العربية الإلكترونية واستخدامها في إندونيسيا - R Taufiqurrochman (Abjadia, 2016)
يهدف هذا البحث معرفة استجابة المدرسين والطلاب في استخدام المعاجم العربية الإلكترونية التي تنقسم على ثلاثة أصناف. الأول: المعاجم الإلكترونية الحاسوبية. والثاني: المعاجم الإلكترونية الهاتيفية. والثالث: المعاجم الإلكترونية للشبكة الدولية. وعدد المستجيبين 150 شخصا. ونتائج هذا البحث: 12% استخدموا المعاجم مرارا، و 55% أحيانا، و 33% لا يستخدمونها بتا. إن أشهر المعاجم الإلكترونية الحاسوبية قاموس "الوافي" لتمام فوائدها. أما المعاجم الإلكترونية الهاتيفية فأشهرها عندهم قاموس "المنور" (عربي-إندونيسي) على شكل الكتاب الإلكنتروني (PDF). والمعجم الإلكتروني الذي زاروه في الشبكة الدولية هو جوجل الترجمة لسهولة الاستخدام. وكان 63% من 150 شخصا يحتاجون إلى المعجم الخاص المشتمل على المفردات المعينة بعلم أو فن خاص. 20% منهم قالوا إن المعاجم الإلكترونية تسهل في ترجمة اللغة العربية بسريع. فلذلك، 10% منهم ادعوا بحاجة ماسة إلى المعاجم الإلكترونية المطورة لتعليم اللغة العربية ليكون حسنا وفعالا.This study aims to investigate the response of the teachers and students on the use of electronic dictionaries Arabic. There are three electronic dictionaries Arabic. First, electronic dictionary software-based computer. Second, mobile-based electronic dictionaries. Third, electronic dictionaries based websites. 150 respondents in this study. The results of this study, 12% admitted to frequently using electronic dictionaries, 55% some times, and 33% never. Computer-based electronic dictionary of the most popular among them is al-Wafi Dictionary for its complete. Mobile-based electronic dictionaries are most often they use in learning Arabic is al-Munawwir Dictionary PDF version. Electronic dictionaries based websites that they visit often is Google Translate for easily accessible. 63 of 150 respondents (42%) claim requires specialized vocabulary of the field of study. 20% of respondents stated that the electronic dictionary Arabic simplify and accelerate the translation of the Arabic Language. Therefore, 10% of them deeply in need of an electronic dictionary. They expect the electronic dictionary Arabic is continuously researched, developed, and manufactured in order to study Arabic in Indonesia is getting better and effective.